Attitudes to inequality 1991 - A Swedish survey - Svallfors, Stefan (Umeå University, 2009)
The survey deals with Swede's attitudes towards inequality. Questions asked are mainly taken from the 1987 'Social inequality' module of the International Social Survey Program (ISSP). Respondents were asked to specify how important different background factors are for the opportunities to get ahead in life. Furthermore they had to state what they believe people in different occupations actually earn, as well as what they considered they should earn. Other questions dealt with income inequalities; factors important when deciding the salary; taxes and how they affect different groups; and how big opposition there are between different social groups in Sweden. Demographic data on respondents such as age, sex, employment, income, marital status, education, religion, political affiliation, and trade union membership also are provided. Questions were also asked about the occupation of the respondent's father and the respondent was asked to compare the status of his/her own occupation with the father's.

Undersökningen behandlar svenskarnas attityder till ojämlikhet och är huvudsakligen en replikation av 1987 års modul i International Social Survey Program (ISSP), vilken genomfördes i tio länder. Respondenterna fick bland annat ange hur viktiga man tyckte olika bakgrundsfaktorer är för att ha framgång i livet. Vidare fick man ange sin uppfattning om olika gruppers löner och om löneskillnader i samhället, vilka faktorer som borde påverka lönen, inställning till skatter och hur olika grupper drabbas, och hur stora motsättningar man anser att det finns mellan olika sociala grupper i Sverige. För respondenten finns uppgifter om utbildning, yrke och inkomst samt uppgifter om faderns yrke och en jämförelse mellan det egna och faderns yrke i statushänseende.
Åsikter om ojämlikhet i Sverige 1991
Keywords: groups; grupper; income distribution; inkomstfördelning; income tax; inkomstskatt; interpersonal conflict; interpersonell konflikt; social inequality; social ojämlikhet; social structure; social struktur; wages; löner; Income, property and investment/saving; Inkomster, egendom och investeringar/sparande; Equality, inequality and social exclusion; Jämlikhet, ojämlikhet och socialt utanförskap; Social behaviour and attitudes; Socialt beteende och attityder; Social conditions and indicators; Sociala förhållanden och indikatorer; Social Sciences; Samhällsvetenskap; Sociology; Sociologi